Sistem Pendukung Keputusan Pemilihan Siswa Berprestasi Menggunakan Metode Preferince Selection Index (PSI) - Alvin Mustofa Kemal Atatur; Khairil Khairil; Abdussalam Al Akbar (UNIVED Press, 2026)
In a school, the ranking of outstanding students is usually only selected based on their final grades, as is the case at SMK 02 Bengkulu City. The selection of outstanding students at SMK 02 Bengkulu City is only based on report card grades ranked 1 to 5. This selection process has many opportunities to make wrong decisions because the student selection process is only based on one aspect, namely the student's final grades, while the attitude and achievement scores obtained outside of school are not taken into consideration as additional criteria for determining students who are considered outstanding and receive scholarships. This means that there is a high probability that the selected outstanding students do not meet the desired standards and do not get the best candidates. The purpose of this study is to provide an alternative way for schools to determine outstanding students so that it is not only based on academic grades, and there is no cheating in the selection of outstanding students. The method used in this study is the Preference Selection Index (PSI) method. The results of this study show that the PSI method can provide the best results from the predetermined criteria and weights.